Narratives of Power and Resistance: Literary Representations of Social Transformation in Post-Globalization Societies - Ahmad Husin; Anthony Mwangi; Faith Chebet (Journal of Humanities Research Sustainability, 2026)
Background. In post-globalization societies, literature has become a critical arena for articulating tensions between hegemonic power structures and emerging forms of resistance. As economic, political, and cultural globalization assume fragmented and uneven trajectories, literary narratives increasingly reflect complex social transformations, identity negotiations, and power asymmetries that are often marginalized in dominant discourses. Purpose. This study aims to examine how literary texts represent power and resistance as interconnected forces shaping social transformation in post-globalization contexts. Method. Employing a qualitative interpretative approach, this study uses critical literary analysis informed by postcolonial theory and cultural studies. Selected contemporary novels from diverse geopolitical regions are analyzed to identify narrative strategies, character constructions, and symbolic representations of power relations and resistance practices. Results. The findings reveal that literary works portray power not solely as an oppressive structure but also as a dynamic process contested through everyday resistance, counter-narratives, and reimagined identities. Literature functions as a space of symbolic resistance, enabling marginalized voices to challenge dominant ideologies and propose alternative social imaginaries. Conclusion. This study concludes that post-globalization literature plays a transformative role by mediating social critique and envisioning possibilities for emancipatory change, thereby contributing to a deeper understanding of contemporary social transformation.